Components of production and productivity of agroecological white oats sown in no-tillage and conventional system - Seidel, Edleusa Pereira (2022)
The present study aimed to evaluate the morphological components and productivity of two agroecological white oat cultivars sown in two soil management systems: no-tillage and conventional system. The experiment was carried out at the Agroecology CVT, belonging to Unioeste in Entre Rios do Oeste, PR. A subplot was divided into two white bird cultivars: Corona and Artemis cultivated in the agroecological system. The cultivars were seeded in talhões, each talhão was divided into five soils, which constituted the repetitions. Approved forams: plant height, panicle compression, diameter of main stem and peduncle, number of spikelets per panicle, number of grains per panicle, number of panicles/m2 and productivity. The development of the bird culture was prejudiced by water deficit during the culture cycle that was only 90.80 mm. Or management of direct and conventional planting of only differently affected the cultivars. The greater diameter of the main stem and hectoliter weight was validated not to cultivate URS Corona, regardless of the management adopted. A higher productivity was observed not cultivating URS Corona, not a conventional-only preparation system with 1581.71 kg ha-1. The average productivity of the white bird cultivated in an agroecological system was 776.75 kg ha-1.